2011
DOI: 10.1111/j.1365-2559.2011.03890.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CRTC1/3-MAML2 fusions on histological classification and prognosis of mucoepidermoid carcinoma

Abstract: Molecular AFIP classification may be useful in predicting the prognosis of patients with MEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 17 publications
2
59
0
7
Order By: Relevance
“…We previously reported that both CRTC1-MAML2-positive and CRTC3-MAML2-positive mucoepidermoid carcinomas are associated with mild histopathological features and a favorable clinical outcome compared with fusion-negative carcinomas. (7,12,13) Our present data show that the X-MAML2 carcinomas might also possess favorable tumor features similar to those positive for CRTC1/3-MAML2 fusions. However, it should be noted that there were minor differences between the three groups, such as differential expression of wild type MAML2 transcripts, lower patient age in the CRTC3-MAML2 fusion group and possibly poorer disease-free survival in CRTC1-MAML2 fusion groups.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…We previously reported that both CRTC1-MAML2-positive and CRTC3-MAML2-positive mucoepidermoid carcinomas are associated with mild histopathological features and a favorable clinical outcome compared with fusion-negative carcinomas. (7,12,13) Our present data show that the X-MAML2 carcinomas might also possess favorable tumor features similar to those positive for CRTC1/3-MAML2 fusions. However, it should be noted that there were minor differences between the three groups, such as differential expression of wild type MAML2 transcripts, lower patient age in the CRTC3-MAML2 fusion group and possibly poorer disease-free survival in CRTC1-MAML2 fusion groups.…”
Section: Discussionsupporting
confidence: 57%
“…A total of 95 cases were included in this study, some of which were also incorporated in our previous studies. (7,12,13) All tumor samples were fixed in formalin and embedded in paraffin. Informed consent was obtained, and the study was approved by the institutional review board of Nagoya City University and conducted in accordance with the Declaration of Helsinki.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…19 When positive for the fusions CRTC1eMAML2 or CRTC3eMAML2, even 'high-risk' patients, including those with a higher histological grade or an advanced clinical stage, showed an excellent prognosis. 20 Thus, it has been proposed that fusionpositive MECs should be regarded as representing a distinctive entity separate from fusion-negative cases. 20 Recently, the EWSR1-POU5F1 fusion gene was documented in mucoepidermoid carcinomas of salivary gland as well as in hidradenoma of skin, providing further evidence for a genetic link between these two tumour types.…”
Section: Introductionmentioning
confidence: 99%